Effect of 4-week ingestion of tomato-based carotenoids on exercise-induced inflammation, muscle damage, and oxidative stress in endurance runners - Nieman, D. C.; Capps, C. L.; Capps, C. R.; Shue, Z. L.; McBride, J. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
This double-blind, randomized, placebo-controlled crossover trial determined if ingestion of a supplement containing a tomato complex with lycopene, phytoene, and phytofluene (T-LPP) and other compounds for 4 weeks would attenuate inflammation, muscle damage, and oxidative stress postexercise and during recovery from a 2-hr running bout that included 30 min of -10% downhill running. Study participants ingested the T-LPP supplement or placebo with the evening meal for 4 weeks prior to running 2 hr at high intensity. Blood samples and delayed onset muscle soreness ratings were taken pre- and post-4-week supplementation, and immediately following the 2-hr run, and then 1-hr, 24-hr, and 48-hr postrun. After a 2-week washout period, participants crossed over to the opposite treatment and repeated all procedures. Plasma lycopene, phytoene, and phytofluene increased significantly in T-LPP compared with placebo (p < .001 for each). Significant time effects were shown for serum creatine kinase, delayed onset muscle soreness, C-reactive protein, myoglobin, 9- and 13-hydroxyoctadecadienoic acids, ferric reducing ability of plasma, and six plasma cytokines (p < .001 for each). The pattern of increase for serum myoglobin differed between T-LPP and placebo (interaction effect, p = .016, with lower levels in T-LPP), but not for creatine kinase, delayed onset muscle soreness, C-reactive protein, the six cytokines, 9- and 13-hydroxyoctadecadienoic acids, and ferric reducing ability of plasma. No significant time or interaction effects were measured for plasma-oxidized low-density lipoprotein or serum 8-hydroxy-2'-deoxyguanosine. In summary, supplementation with T-LPP over a 4-week period increased plasma carotenoid levels 73% and attenuated postexercise increases in the muscle damage biomarker myoglobin, but not inflammation and oxidative stress.